Research at Grass Roots: A Primer for the caring professions - Annatjie Botes (AOSIS, 1997)
The combination of this new research textbook with Johan Mouton's understanding of Social Research is the solution for research in the caring professions of social sciences. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.